ANALISIS PEMASARAN GAMBIR (UNCARIA GAMBIR) DI NAGARI SIALANG KECAMATAN KAPUR IX KABUPATEN LIMA PULUH KOTA - Suardi Tarumun; Eliza Eliza; Rizki Kurniawan (Indonesian Journal of Agricultural Economics, 2019)
Indonesia is the biggest gambier export country in the world. Kapur IX subdistrict is the largest gambier production (40,20%) in lima puluh kota regency, especially in west sumatra, mean while gambier become main job for most of people in the regional. The purpose of the research is to analyze function, duct, cost, profit, margin, level market efficient, and the advantage for gambier farmers, analyze the market problem in nagari sialang kapur IX district lima puluh kota regency. The location of research use purposive sampling is nagari sialang which center of gambier production. Respondent of the research is gambier farmers and all of marketing institution in gambier marketing. Result of the research shows gambier marketing function such as exchange function, physical function, and facility and two gambier marketing ducts; marketing ducts I (76,67%) farmers sell to the collector, then sell to big seller, and marketing duct II (23,33%) farmer sell to the big sell. Cost of duct I is Rp 6.332/kg, profit is Rp 21.775/kg, margin Rp 28.087/kg efficient level is 7,63% and for farmer Rp 54.578/kg. Marketing cost of duct II is RP 3.734/kg, profit Rp 11.123/kg, margin Rp 14.857/kg, level efficient is 4.95%, for farmer is Rp 60.163. The problem in marketing of gambier is  mixture of fertilizer for planting gambier, fluctuation price of gambier, bad quality of gambier.